Association Between Family Physical Violence Victimization and Food Consumption Among Brazilian Adolescents - Marques, Emanuele Souza (Journal of interpersonal violence, 2021)
Few studies have evaluated the relationship between stressful events, such as child abuse and food consumption. Thus, the objective of this study is to assess whether family physical violence victimization is associated with food consumption in adolescents. We used data from the Brazilian National Adolescent School-based Health Survey, carried out in 2015, in a representative sample of 102,072 students attending ninth grade from public and private schools. We used Venn diagrams and logistic regression analysis to, respectively, graphically represent and evaluate the association between the consumption of ultra-processed food (soft drinks, sweets/candies, and salty biscuits, packaged snacks, or processed meat) and in natura food (beans, fruits and vegetables) with victimization from family physical violence. We found a lower consumption of in natura and higher consumption of ultra-processed foods among adolescent victims when compared with nonvictims of family physical violence. The probability of consuming 4 or more times a week increased by 44% for salty biscuits, packaged snacks, or processed meats; 38% for soft drinks; and 22% for sweets among adolescents who reported violence. On the contrary, the probability of consuming 4 or more times a week decreased by 25% for beans, 19% for vegetables, and 13% for fruits among adolescent victims of family physical violence. We conclude that family physical violence victimization is associated with high consumption of ultra-processed food and low consumption of in natura food among Brazilian adolescents. Therefore, issues related to violence in childhood and adolescence should be addressed in interventions aimed at altering food consumption and consequent prevention, control, and treatment of nutrition-related outcomes to increase their effectiveness.